Validity of Panoramic Indices to Evaluate the Association of Bone Mineral Density with Morphology of the Mandible in Osteoporotic Patients - Hajipour, Masoume; Safi, Yaser; Kadkhodazadeh, Mahdi; Mirakhori, Mahdieh; Amid, Reza; Dehghan, Ali (Journal of Dental School, 2019)
Objective: Osteoporosis is the most common metabolic disease of the bone decreasing bone mineral density (BMD) particularly in postmenopausal women. On the other hand, panoramic radiography has several applications in dentistry. It appears that by calculating some indices on panoramic radiographs, we may be able to predict the risk of osteoporosis in high-risk individuals. The present study was conducted to determine the correlation of skeletal pattern of bone and the morphology of the mandible in osteoporotic patients presenting to the Osteoporosis Clinic of Khatamolanbia Hospital and Imam Khomeini Dental Clinic in Yazd. Methods: This descriptive, analytical, cross-sectional study was conducted on 70 women aged over 45 years, whom were selected from the above-mentioned centers. The gonialangle (GA), gonial index (GI), antegonial angle (AA), mental index (MI), antegonial index (AI) and antegonial depth (AD) were calculated on panoramic radiographs of patients and their BMD was measured in the lumbar area and femoral areas using dual X-ray absorptiometry (DXA). The correlation of panoramic indices with BMD was assessed using Spearman and Pearson’s correlation tests. The difference in BMD values in different morphological patterns of the inferior cortex of the mandible was analyzed by Student t-test and in different thicknesses of the cortex using one-way ANOVA. Results: The morphology of the inferior cortex was C1 in 62.9% and C2 in 37.1%. The cortex was thin in 24.3%, moderately thick in 32.9% and thick in 42.9%. Lumbar BMD was 0.92 (0.14) and 0.75 (0.15) g/cm2, in C1 and C2, respectively (p<0.001). Femoral BMD was 0.81 (0.13) and 0.66 (0.09) g/cm2 in C1 and C2, respectively (p<0.001). No significant association was found between GI, AI, GA, AA and AD (based on the estimates made on panoramic radiographs) with the BMD (based on DXA estimates). Conclusion: Use of mandibular cortex indices on panoramic radiographs may be efficient for assessment of osteoporosis. However, further multicenter studies on larger sample sizes are required.